2020
DOI: 10.1177/1940161219898055
|View full text |Cite
|
Sign up to set email alerts
|

Who Uses Fact-Checking Sites? The Impact of Demographics, Political Antecedents, and Media Use on Fact-Checking Site Awareness, Attitudes, and Behavior

Abstract: This study examines audience relationships to fact-checking sites in the United States. Focus is placed on predictors of audience awareness of, attitudes toward, and visits to such sites within a stage model framework drawn from the persuasive message literature. Analysis of survey data from a U.S. sample shows that liberals and liberal/mainstream news consumers are more aware of, positive toward, and likely to report using fact-checking sites. Conservatives are less positive and conservative news consumers se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 24 publications
7
31
1
14
Order By: Relevance
“…The PCA yielded four components with eigenvalues greater than 1.0: mainstream media, such as center-leftleaning newspapers and magazines, center-right leaning newspapers and magazines, liberal websites, and NPR/PBS; TV sources, such as ABC, NBC, and CNN; medical information sources, such as WebMD, doctors, and the CDC website; and conservative news sources, such as Fox News and conservative talk radio. These repertoires of source use align with prior research in the United States (e.g., Mourão et al, 2018;Robertson et al, 2020).…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…The PCA yielded four components with eigenvalues greater than 1.0: mainstream media, such as center-leftleaning newspapers and magazines, center-right leaning newspapers and magazines, liberal websites, and NPR/PBS; TV sources, such as ABC, NBC, and CNN; medical information sources, such as WebMD, doctors, and the CDC website; and conservative news sources, such as Fox News and conservative talk radio. These repertoires of source use align with prior research in the United States (e.g., Mourão et al, 2018;Robertson et al, 2020).…”
Section: Methodssupporting
confidence: 79%
“…The benefit of this approach is that it allows for a degree of specificity when asking survey respondents about media use while not overwhelming them with a large number of response options. It is also theoretically and empirically driven, rooted in prior works that have identified sets of ideologically and interest-based news repertoires in the United States across media sources and platforms (Mourão et al, 2018;Robertson et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these findings suggest that fact-checking is failing to reach precisely those politically uninterested and disaffected citizens that are arguably most vulnerable to misinformation and disinformation. Moreover, there are clear signs that political cleavages similar to those identified by previous research in the United States (Robertson et al 2020) shape attitudes toward fact-checking in Europe as well. In most countries, satisfaction with the European Union is positively associated with favorability toward fact-checking.…”
Section: Clarifying Challenges Assessing Solutions: This Special Issuesupporting
confidence: 56%
“…Motivations to share fact-checks are also unclear. Previous work from political contexts in the United States showed that motivations to share fact-checks could be linked to age, ideology, and political behaviours ( Amazeen et al, 2019 ), with more politically liberal users as the primary consumer of fact-checking materials ( Robertson et al, 2020 ). During COVID-19, concern for health and safety was correlated with a higher acceptance of fact-checking in the United States, with greater effect sizes for republicans ( Rich et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%